1996
DOI: 10.1002/eji.1830260106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CD28‐B7.1 and B7.2 functional interaction in resting human T cells: Phosphatidylinositol 3‐kinase association to CD28 and cytokine production

Abstract: CD28 is a 44kDa homodimer present on T cells providing an important costimulatory signal for T cell proliferation, cytokine production and cytokine receptor expression. CD28 activation is mediated by interaction with its counter-receptors, B7.1/CD80 and B7.2/B70/CD86. The biochemical basis of these co-stimulatory signals are still poorly understood, particularly in resting T cells. However, various biochemical pathways such as tyrosine phosphorylation, phospholipase C, sphingomyelinase and phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 67 publications
1
20
0
Order By: Relevance
“…Truitt et al (17) also found that wortmannin did not inhibit CD28-dependent IL-2 production from freshly isolated murine CD4 ϩ T cells. On the contrary, wortmannin was reported to inhibit CD28-mediated costimulation of IL-2 in human primary T cells (13)(14)(15). One of the possible explanations for the apparent discrepancies among these reports may be the nature of the cell used in the respective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Truitt et al (17) also found that wortmannin did not inhibit CD28-dependent IL-2 production from freshly isolated murine CD4 ϩ T cells. On the contrary, wortmannin was reported to inhibit CD28-mediated costimulation of IL-2 in human primary T cells (13)(14)(15). One of the possible explanations for the apparent discrepancies among these reports may be the nature of the cell used in the respective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since the T cell responses that are induced by CD28-mediated cosignaling overlap the reported functions of PI3K in lymphocyte activation, it is conceivable that PI3K may be the critical signaling molecule in T cell costimulation. For example, wortmannin, a potent inhibitor of PI3K, is reported to inhibit CD28-dependent IL-2 production in human peripheral T cells (13)(14)(15). Furthermore, CD28 mutants, which are unable to bind to PI3K, demonstrate that PI3K is required for CD28-mediated IL-2 production in mouse T cell hybridoma cell lines (4,16).…”
mentioning
confidence: 99%
“…Using purified human T cells, Olive and colleagues (39) also demonstrated that both CD80 and CD86 induced the SH2-dependent association of CD28 with PI3-K. However, they further demonstrated that wortmannin, a specific inhibitor of lipid kinase activity of PI3-K via binding to the p110 subunit, inhibited CD80 costimulation of IL-2 production more efficiently than CD86 costimulation (IC 50 25 and 110 nM, respectively) (39). This suggested that the dependence on PI3 lipid kinase activity of CD80 and CD86 stimulation differed, an observation consistent with our results.…”
Section: Stimulation With Cd80 or Cd86 Induces The In Vivo Tyrosine Pmentioning
confidence: 99%
“…27,28 Band intensity was quantified by densitometry using a Biolmage analyzer (Biolmage, Palo Alto, CA, USA). Normalized level of expression of a specific protein was given as the ratio (optical density of the specific protein/optical density of p 85), and standardized results were expressed in arbitrary units.…”
Section: Quantification Of Protein Expressionmentioning
confidence: 99%